PRAISE AND FEEDBACK IN THE SECONDARY EFL CLASSROOM - Salameh, Walid (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
This study aims at investigating praise and feedback practices in the EFL classroom. The method implemented in this study is qualitative method. The researcher conducted the study using observation as the main tool. The researcher has chosen two classes from two schools, grade four class from the primary school and a class from a secondary school where the students and teachers from the two different observed schools were involved. Through the findings of this study regarding praise and feedback in the EFL classroom, it is crucial to use them in classrooms in a proper way. Besides; praise and feedback encourage and motivate students mainly if praise is targeted and not used just randomly. Teachers should use positive specified praise if they are impressed by an answer or behaviour, Furthermore, the study revealed that feedback should be given regularly whether verbal or non-verbal. Teachers should care about the selected feedback they are going to use, in other words, for young children, ability feedback is preferable while for older ones, effort feedback is preferred.